Ongoing training for efl teachers based on their specialist needs. case: Colegio Español Padre Arrupe, Academic Year 2016. - Flores Alas, Hilda Jacobed; Mendoza Palacios, Cristian Ademir; Zavaleta Méndez, Elizama Abigail (2024)
The present work is part of a research project called "Ongoing training for EFL teachers based on their specialist needs. Case: Colegio Español Padre Arrupe, academic year 2016", presented by the students Hilda Jacobed Flores Alas, Cristian Ademir Mendoza Palacios and Elizama Abigail Zavaleta Mendez under supervision from M.Ed. Ricardo Garay Salinas member of the Foreing Language Department of the University of El Salvador in order to obtain the degree of bachelor of arts in English with emphasis in teaching. The objective of this undergraduate research is to identify the areas of opportunity of the teachers in service in English language teaching area of the different levels of the Colegio Español Padre Arrupe to emphasize the importance of a process of ongoing training for the teachers of this institution, in particular for teachers who are specialists in the English language and its relation with the student's academic achievement, and based on those finding to propose projects aimed at benefiting students, thereby improving the level of educational quality in the English language, from the perspective of teachers.